PELATIHAN KEBERSYUKURAN UNTUK MENINGKATKAN KUALITAS HIDUP PADA WANITA DISABILITAS FISIK - Desta Israwanda; Siti Urbayatun; Elli Nur Hayati (Universitas Islam Indonesia, 2019)
This study examines the effect of gratitude training to improve the quality of life in women with physical disabilities. Participans of this study were 30 participants, there are 15 participants in each group. The data were analyzed using mixed design anova.The result showed a very significant difference in quality of life’s score at pretest, posttest, and follow up between the experimental and controlled group (F=56,586, p=0,000 (p<0,05)).In addition, there was significant changes in quality of life’s score at experimental group (MD=-15,467 and p=0,000.Those findings indicate that there was increase in the level quality of life in the experimental group.Furthermore,gratitude training contributed 84,3% to the increase quality of life.of women with physical disabilities.